Mechanical Thrombectomy for Acute Ischemic Stroke in Southeast Asian Countries: A Systematic Review and Meta-analysis - Ghifari, Muhammad Ramadhan; Deskianditya, Resa Budi; Dewi, Lisa Larosma (Asian Journal of Neurosurgery, 2025)
This study aims to systematically examine the results of mechanical thrombectomy (MT) in managing acute ischemic stroke (AIS) among patients in Southeast Asia, addressing the current gap in region-specific data. A thorough search was performed in Scopus and PubMed databases from inception through February 2025, with additional sources identified through citation tracking. This review included observational studies involving adult AIS patients who underwent MT. The study quality was appraised using the Newcastle-Ottawa Scale. Key clinical endpoints assessed included favorable functional independence mRS scores (0–2), successful recanalization (TICI 2b/3), incidence of symptomatic intracranial hemorrhage (sICH), and 90-day mortality. Outcome data were synthesized using pooled proportion estimates under a random-effects modeling. Statistical heterogeneity was evaluated using the I2 metric. A total of 12 observational studies encompassing 1,037 patients were included. The studies were from Vietnam, Singapore, Indonesia, Philippines, and Thailand. The pooled proportion of patients achieving functional independence mRS (0–2) was 48.3% (95% CI: 38.9 -57.8%; I2 = 88.06%), while successful recanalization was achieved in 72.3% (95% CI: 63.3–81.2%; I2 = 91.86%). The rates of sICH and mortality were 7.95% (95% CI: 4.9–11%; I2 = 64.85%) and 17.3% (95%CI: 11 -23.6%; I2 = 80.69%), respectively. Subgroup analysis showed that prospective studies had better outcomes than retrospective studies, with higher functional independence and lower mortality rates. outcomes varied across countries, likely reflecting differences in healthcare infrastructure, access to thrombectomy-capable centers, and stroke system maturity. Mechanical thrombectomy in Southeast Asia yields effectiveness and safety outcomes comparable to those observed in Western high-income countries, despite resource limitations. However, regional variations highlight the influence of healthcare infrastructure on stroke outcomes. Expanding MT programs, improving early access to care, and addressing financial barriers are essential steps toward optimizing regional stroke care.
Keywords: mechanical thrombectomy; acute ischemic stroke; stroke; Southeast Asia; endovascular thrombectomy